Traditional Marriage System (Fa'ha) in the Study of Citizenship Education in East Tamher State, Kesuy Watubela District - Kelkulat, Sahrul; Abas, Aisa; Tuharea, Jimiati (CV. Rayyan Dwi Bharata, 2024)
Marriage in the East Tamher community begins with an engagement process which is carried out through an application process. After the application process is complete, the man comes to meet the woman's family to discuss the marriage dowry. After determining the dowry, the man brings 5 trays containing five dowries, the five dowries are marked with five hamlets and seven etar (clans), after the process of handing over the 5 trays has been completed, the traditional marriage has been carried out, followed by a religious marriage. Fa'ha marriage is a marriage based on the customs that apply in East Tamher. Fa'ha itself is a regional language which means marriage. The marriage customs of the Tamher Timur community are no longer preserved, most of these people choose to marry by only paying a dowry without having to carry out a traditional marriage. This means that habits arise which are carried out repeatedly, causing the marriage tradition to disappear by itself. The type of research used in this research is descriptive qualitative where the data is obtained through the process of observation and interviews and the research data is analyzed qualitatively. The traditional marriage process will be carried out by the community, namely first sitting down to talk about customs because the people of East Tamher State believe that custom is something sacred and is inherent in the people of the State because it is also something that culture is a whole system of ideas, actions and results of human work in the framework of community life that belongs to humans and students. Traditional marriages viewed from citizenship education show that traditional marriages in East Tamher State are no longer preserved. Marriages carried out in the people of East Tamher State are carried out like marriages in society in general. If viewed from citizenship education, it is something that is not good to carry out continuously because traditional marriages is a tradition that must be maintained and preserved.